Do You Still Watch the News on TV? Examining TV News Viewing among Malaysians Today - Collin, Jerome; Ting, Su Hie; Ahmad Junaidi, Ahmad Hadzmy; Humaira, Raslie (2023)
Television has long been recognized as a significant source of news for the mass public. Research has shown the rise and fall in the public viewing of news on television due to the advancement of digital technologies. Younger audiences, in particular, have turned to social media to access news and this trend is rapidly growing. The current study sought to ascertain if this was the case for people who may continue to watch television news despite the said technological advances. Interviews with 40 individuals from the East Malaysian state of Sarawak were conducted to gather their views on whether people living in Malaysia still watch television news and the factors contributing to this trend. The findings show that television remains an integral part of the participants' everyday lives and that it continues to be an important medium for disseminating news. While the younger participants reported that they regularly accessed news on social media, they still turned to television as a more reliable and trustworthy news source. The findings revealed several factors that contributed to television news viewing among the participants: the social-familial, the situational-environmental, the personal, and the technological. The findings shed useful insights into the current trend of television news viewing among the mass public as the world is gradually ending the COVID-19 pandemic and transitioning into endemic while experiencing news consumption on digital media.